Ellagic Acid Triggers the Necrosis of Differentiated Human Enterocytes Exposed to 3-Nitro-Tyrosine: An MS-Based Proteomic Study - Silvia Díaz-Velasco; Josué Delgado; Fernando J. Peña; Mario Estévez (MDPI AG, 2022)
To study the molecular basis of the toxicological effect of a dietary nitrosated amino acid, namely, 3-nitrotyrosine (3-NT), differentiated human enterocytes were exposed to dietary concentrations of this species (200 μM) and analyzed for flow cytometry, protein oxidation markers and MS-based proteomics. The possible protective role of a dietary phytochemical, ellagic acid (EA) (200 μM), was also tested. The results revealed that cell viability was significantly affected by exposure to 3-NT, with a concomitant significant increase in necrosis (p < 0.05). 3-NT affected several biological processes, such as histocompatibility complex class II (MHC class II), and pathways related to type 3 metabotropic glutamate receptors binding. Addition of EA to 3-NT-treated cells stimulated the toxicological effects of the latter by reducing the abundance of proteins involved in mitochondrial conformation. These results emphasize the impact of dietary nitrosated amino acids in intestinal cell physiology and warn about the potential negative effects of ellagic acid when combined with noxious metabolites.